Micro aneurysms detection using artificial neural networks - Reddy, S. Srinivasa; Suman, Dr. M.; Prakash, Dr. K. Naga (International Journal of Engineering & Technology, 2018)
Blindness caused by diabetic related issues was increasing day by day, it only affects the eyes but also other sensory, internal and external organs of the body. The major cause of blindness is due to high glucose levels in the nerves nearby optic disc. Diabetic issues of eyes were known as diabetic retinopathy. For reducing the effect of diabetes in the functionality of the eyes regular screening and identification of problems while they were in the initial stages was very important. Early identification of abnormalities in the eyes such as damage to the vessels of eye, exudates, and microaneurysms will help to reduce the effect of diabetic retinopathy. This paper deals in identifying all the three procedures differently and leaves in result damage in the exudates.